Balićžunićite, Bi2O(SO4)2, a new fumarole mineral from La Fossa crater, Vulcano, Aeolian Islands, Italy. (August 2014) - Pinto, D.; Garavelli, A.; Mitolo, D.
Abstract: Balićžunićite, ideally Bi2 O(SO4 )2, is a new mineral found as a high-temperature fumarole sublimate ( T = 600°C) at La Fossa crater, Vulcano, Aeolian Islands, Italy. It occurs as aggregates of mm-sized prismatic and elongated crystals (∼50 μm across and up to 200 μm long) associated with anglesite, leguernite, one other potentially new Bi-oxysulfate mineral, lillianite, galenobismutite, bismoclite, Cd-rich sphalerite, wurtzite, pyrite and pyrrhotite. Balićžunićite is colourless to white or pale brown, transparent and non-fluorescent. It has a vitreous lustre and a white streak. Electron microprobe analysis gives the following average chemical composition (wt.%): Bi2 O3 68.68 and SO3 23.73, total 92.41. The empirical chemical formula, calculated on the basis of 9 anions p.f.u., is Bi1.99 S2 O9 . The calculated density is 5.911 g/cm 3 . Balićžunićite is triclinic, space group P, with a 6.7386(3), b 11.1844(5), c 14.1754(7) Å, α 80.082(2)°, β 88.462(2)°, γ 89.517(2)°, V = 1052.01(8) Å 3 and Z = 6. The six strongest reflections in the X-ray powder-diffraction data [ d in Å( I ) ( hkl )] are: 3.146 (100) (033), 3.486 (21) (004), 3.409 (12) (0 1), 3.366 (7) (200), 5.562 (4) ( 11), 5.433 (4) (111). Balićžunićite is the natural analogue of the stable low-temperature a form of synthetic Bi2 O(SO4 )2 . The name is in honour of Tonci Balić-Žunić(born 1952), Professor of Mineralogy at the Natural History Museum of the University of Cophenagen. Both the mineral and the mineral name have been approved by the IMA-CNMNC Commission (IMA2012-098).